(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The study examined the effects of gender and location on social studies students’ academic achievement in an interactive multimedia learning environment: empirical evidence from Zaria Education Zone. The design of the study was the non-equivalent pre-test post-test control group type of quasi-experiment. The population of the study consisted of JSSIII Social Studies students in Zaria Education Zone, Kaduna State. There is a total number of 26322 JSSIII students consisting of 14178 male and 12144 female students in the study area. The participating schools were purposively selected. Intact classes of 349 were used. The study used two instructional packages called Social Studies Interactive Multimedia Package (SOSIMP) to assist in the teaching of the experimental group and Social Studies Conventional Lecture Method (SOSCOLM) for the control group. The Social Studies Achievement Test (SSAT) was the data collection instrument. The content and construct validity of the instrument were determined by experts in social studies and test and measurement. The reliability coefficient index of the instrument was 0.786. Arithmetic means and standard deviations were used to answer the questions posed, while two-way analysis of variance (ANOVA) was used to test the null hypotheses at 0.05 alpha. The study found that gender has a significant effect on social studies students’ academic achievement in an interactive multimedia learning environment and that school location has no significant effect on students’ academic achievement in an interactive multimedia instruction learning environment. In the light of the foregoing, it is recommended that social studies teachers should employ interactive multimedia instruction in boys’ schools and that interactive multimedia instruction should be the chosen instructional strategy for teaching social studies in urban and rural secondary schools in Zaria Education Zone, Kaduna State, Nigeria.